1996
DOI: 10.1007/s004240050270
|View full text |Cite
|
Sign up to set email alerts
|

Differences in α 2 -adrenoceptor modulation of calcium channels in vascular smooth muscle cells of male and female rats

Abstract: Effects of the alpha2-adrenergic agonist clonidine on current through Ca2+ channels was recorded from vascular smooth muscle cells isolated from tail arteries and aortae of male and female rats. The average Ba2+ current in control was not significantly different between males and females; however, clonidine (1 microM) enhanced Ba2+ current through Ca2+ channels in cells from females, but not from males. The greater sensitivity of vascular smooth muscle cells to clonidine may underlie different contractile resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Chotani et al (2000) demonstrated that cold-induced amplification of smooth muscle a 2 -adrenoceptors reactivity in skin vessel walls is mediated by a 2C -adrenoceptors, a subtype of a 2 -adrenoceptors that are normally silent in cutaneous arteries. Furthermore, it has been repeatedly shown that animal vascular preparations exhibit significant gender difference in response to adrenergic stimulation (Mercuro et al, 1999;Vargas et al, 1995;Li et al, 1997;Song et al, 1996;Nevala et al, 1996). The greater role in gender specificity has been attributed to the mechanism of a 2 -adrenoceptors (Freedman et al, 1987;Tejera et al, 1999).…”
Section: Introductionmentioning
confidence: 94%
“…Chotani et al (2000) demonstrated that cold-induced amplification of smooth muscle a 2 -adrenoceptors reactivity in skin vessel walls is mediated by a 2C -adrenoceptors, a subtype of a 2 -adrenoceptors that are normally silent in cutaneous arteries. Furthermore, it has been repeatedly shown that animal vascular preparations exhibit significant gender difference in response to adrenergic stimulation (Mercuro et al, 1999;Vargas et al, 1995;Li et al, 1997;Song et al, 1996;Nevala et al, 1996). The greater role in gender specificity has been attributed to the mechanism of a 2 -adrenoceptors (Freedman et al, 1987;Tejera et al, 1999).…”
Section: Introductionmentioning
confidence: 94%